Impact of Dietary Supplementation with Moringa oleifera Leaves on Performance, Meat Characteristics, Oxidative Stability, and Fatty Acid Profile in Growing Rabbits - Selim, Shaimaa (Animals (Basel), 2021)
SIMPLE SUMMARY: Rabbit meat is mostly preferred by consumers owing to its high nutritive value and potential health benefits. However, rabbit meat is commonly more prone to lipid peroxidation during storage, with negative effects on quality traits of meat, due to its elevated level of unsaturation of fatty acids. Moringa oleifera leaves have gained great interest owing to their high nutritional value and low anti-nutritional factors. Moringa oleifera leaves could possibly avoid oxidation damage and exhibit antioxidant activities that can conquer free radicals and reactive oxygen species synthesis. Therefore, the objective of the current study was to evaluate the effects of feeding Moringa oleifera leaves on performance, carcass characteristics, antioxidant capacity, blood biochemical constituents, meat quality, and fatty acids profile of growing rabbits. Moringa oleifera leaves supplementation improved weight gain, feed conversion ratio, antioxidant status, and meat quality characteristics. Dietary Moringa oleifera leaves supplementation enhanced PUFA contents, n-3 fatty acid, crude protein, and color of meat, but lowered the relative content of ether extract of the meat. Our findings suggested that Moringa oleifera could be used at a level of 1.5 g/kg of the growing rabbits’ diets with beneficial impacts on performance and the nutritional value of the meat. ABSTRACT: Moringa oleifera leaves (MOL) have gained great interest as a non-traditional feed ingredient due to their unique nutritional value. Therefore, the objective of the current study was to evaluate the effects of graded dietary supplementation levels with MOL on performance, carcass characteristics, antioxidant capacity, blood biochemical constituents, meat quality, and fatty acids profile of growing rabbits. A total of 120 weaned New Zealand white rabbits (6 weeks old) were randomly allotted into 4 dietary groups with 5 replicates each (n = 6), which were fed for 42 days with a basal diet as control or 3 experimental diets supplemented with 5, 10, or 15 g/kg MOL. The results showed that, compared to the control group, the dietary inclusion of MOL at a level of 10 and 15 g/kg DM linearly increased (p < 0.01) final live weight (2403.3 and 2498.2 vs. 2166.6) and average daily weight gain (36.5 and 35.51 g/d vs. 28.72 g/d), and enhanced feed conversion ratio (2.49 and 2.50 vs. 3.14). The dietary supplementation with MOL linearly increased dressing out percentage, spleen index, intestinal length, and decreased abdominal fat index (p < 0.01). Greater serum levels of total protein and globulin, but lower alanine aminotransferase and aspartate aminotransferase were observed in the MOL-fed rabbits (p < 0.01). Serum levels of total triglycerides, cholesterol, and low-density lipoprotein (p < 0.05) were decreased linearly and quadratically in the MOL groups compared with the control. Glutathione peroxidase activity increased (p < 0.01), whereas malondialdehyde decreased (p < 0.01) linearly and quadratically in both serum and meat, in response to dietary MOL supplementation. Dietary MOL supplementation increased the meat crude protein content but lowered the relative content of ether extract in the meat (p < 0.05). The relative content of the meat n-3 PUFA was increased by about 33.71%, 29.46%, and 24.36% for the MOL(0.5%,) MOL(1%,) and MOL(1.5%) groups compared to control. In conclusion, MOL could be used at a level of 1.5g/kg of the growing rabbits’ diets with beneficial impacts on performance, antioxidant capacity, and the nutritional value of the meat.